Reconstruction of a small defect of the lower vermilion adjacent to white roll using a modified O-Z flap - Kim, Hong Il; Kim, Ho Sung; Park, Jin Hyung; Yi, Hyung Suk; Kim, Yoon Soo; Kim, Hyo Young (Archives of craniofacial surgery, 2021)
Reconstruction of lip defects is important because the lips play an important role in maintaining aesthetic facial balance, facial expressions, and speech. There are various methods of lip reconstruction such as primary repair, skin grafting, and utilization of local and free flaps. It is important to select a proper reconstruction method according to the size and location of lip defect. Failure to select an appropriate method may result in distortion, color mismatch, sensory loss, and aesthetic imbalance. Herein we present a case of successful aesthetic reconstruction of the lower vermilion. We removed a venous malformation, which was limited to the lower vermilion and adjacent to the white roll, and repaired the defect using the modified O-Z flap.Reconstruction of lip defects is important because the lips play an important role in maintaining aesthetic facial balance, facial expressions, and speech. There are various methods of lip reconstruction such as primary repair, skin grafting, and utilization of local and free flaps. It is important to select a proper reconstruction method according to the size and location of lip defect. Failure to select an appropriate method may result in distortion, color mismatch, sensory loss, and aesthetic imbalance. Herein we present a case of successful aesthetic reconstruction of the lower vermilion. We removed a venous malformation, which was limited to the lower vermilion and adjacent to the white roll, and repaired the defect using the modified O-Z flap.